The bolometric quasar luminosity function at z = 0–7. Issue 3 (20th May 2020) - Shen, Xuejian; Hopkins, Philip F; Faucher-Giguère, Claude-André; Alexander, D M; Richards, Gordon T; Ross, Nicholas P; Hickox, R C
ABSTRACT: In this paper, we provide updated constraints on the bolometric quasar luminosity function (QLF) from z  = 0 to z  = 7. The constraints are based on an observational compilation that includes observations in the rest-frame IR, B band, UV, soft, and hard X-ray in past decades. Our method follows Hopkins et al. with an updated quasar SED model and bolometric and extinction corrections. The new best-fitting bolometric quasar luminosity function behaves qualitatively different from the old Hopkins model at high redshift. Compared with the old model, the number density normalization decreases towards higher redshift and the bright-end slope is steeper at z  ≳ 2. Due to the paucity of measurements at the faint end, the faint end slope at z  ≳ 5 is quite uncertain. We present two models, one featuring a progressively steeper faint-end slope at higher redshift and the other featuring a shallow faint-end slope at z  ≳ 5. Further multiband observations of the faint-end QLF are needed to distinguish between these models. The evolutionary pattern of the bolometric QLF can be interpreted as an early phase likely dominated by the hierarchical assembly of structures and a late phase likely dominated by the quenching of galaxies. We explore the implications of this model on the ionizing photon production by quasars, the CXB spectrum, the SMBH mass density, and mass functions. The predicted hydrogen photoionization rate contributed by quasars is subdominant during the epoch of reionization and only becomes important at z ≲ 3. The predicted CXB spectrum, cosmic SMBH mass density, and SMBH mass function are generally consistent with existing observations.